Biphasic anatase-brookite nanoparticles prepared by sol–gel complex synthesis and their photocatalytic activity in hydrogen production. (23rd February 2015) - Cihlar, Jaroslav; Kasparek, Vit; Kralova, Marcela; Castkova, Klara
Abstract Titanium tetraisopropoxide was used as the precursor in the preparation of TiO2 nanoparticles via sol–gel complex synthesis. The complex-forming (chelate-forming) substances used were glycine, EDTA, acetylacetone, and hydroxycarboxylic acids (lactic acid – LA, citric acid – CA, tartaric acid – TA) and their salts (sodium citrate – CA-Na, ammonium citrate – CA-NH4, lithium lactate – LA-Li). Biphasic anatase-brookite nanoparticles were prepared by hydrothermal and solid-state reactions. The specific surface of the particles ranged from 202 to 292 m2/g. Their composition was studied by means of X-ray diffraction. The nanoparticles were studied using differential scanning calorimetry and thermogravimetric analysis. The widths of band gaps were examined using UV–VIS spectroscopy. The Eg values of biphasic TiO2 were in the range from 3.08 to 3.21 eV. The photocatalytic activity of the samples prepared was tested on hydrogen production. The maximum rate of H2 evolution was catalysed by anatase-brookite nanoparticles with 36% of brookite, which were prepared using lactic acid. The minimum rate of H2 evolution was observed in the presence of particles of anatase prepared by means of acetylacetone. Cooperative behaviour of the anatase and brookite phases was observed in the nanoparticles, which retarded the recombination of holes and electrons and led to a photocatalytic activity that was higher than the activities of the two separate phases.